2011
DOI: 10.30638/eemj.2011.169
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of Pet Waste as Thermoplastic Composites

Abstract: Composite manufacturing from plastic wastes of polyethylene terephthalate (PET) type, sand-blasting represents a material recovery of the wastes. This process can be achieved, with the purpose of reducing the material consumption which is in deficit, production costs, and the duration of the technological processes. Thermoplastics composites obtained by a melting process at 170-200 o C, wastes incorporation and solidification in forms replace successfully the thermo rigid composites obtained from resins after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The resulting composites appear to be suitable for rigid, thin-walled, temperature-stable parts (Slieptsova et al , 2016). The range of processing parameters and possible material combinations appear to be quite wide, as other authors reported that 0.62/1.22 mix of PET with contaminated blasting sand reached values as high as 87 MPa in compression and 27 MPa in flex, with temperature of processing extruder set between 185 and 195°C (Dumitrescu et al , 2011).…”
Section: State Of the Artmentioning
confidence: 99%
“…The resulting composites appear to be suitable for rigid, thin-walled, temperature-stable parts (Slieptsova et al , 2016). The range of processing parameters and possible material combinations appear to be quite wide, as other authors reported that 0.62/1.22 mix of PET with contaminated blasting sand reached values as high as 87 MPa in compression and 27 MPa in flex, with temperature of processing extruder set between 185 and 195°C (Dumitrescu et al , 2011).…”
Section: State Of the Artmentioning
confidence: 99%
“…In addition, aminolysis or ammonolysis of the polymer affords valuable monomers which are relevant for production of polyurethane [5,6]. However, the feasibility of the chemolytic depolymerization of PET waste is quite low at the moment due to the harsh reaction conditions required for the polymer scission as well as due the contamination of the products with metal salts from the used catalysts [7][8][9]. Organic catalysts were reported as attractive alternatives to traditional organometallic salts due to low working temperature and selective polymerization/depolymerization reactions [10][11][12][13][14][15][16].…”
mentioning
confidence: 99%